Doping two-dimensional materials: ultra-sensitive sensors, band gap tuning and ferromagnetic monolayers. Issue 2 (17th January 2017) - Feng, Simin; Lin, Zhong; Gan, Xin; Lv, Ruitao; Terrones, Mauricio
Abstract : Well-designed defects can lead to unprecedented properties and interesting applications. For example, heteroatom-doped graphene exhibits enhanced Raman scattering for ultrasensitive detection of certain molecules. Abstract : The successful isolation of graphene from graphite in 2004 opened up new avenues to study two-dimensional (2D) systems from layered materials. Since then, research on 2D materials, including graphene, hexagonal-BN (h-BN), transition metal dichalcogenides (TMDs) and black phosphorous, has been extensive, thus leading to various possible applications in the fields of optoelectronics, biomedicine, spintronics, electrochemistry, energy storage and catalysis. However, certain barriers still need to be overcome when dealing with real applications, such as graphene's lack of a bandgap, restricting its use in semiconductor electronics. In this context, a possible solution is to tailor the electronic and optical properties of 2D materials by introducing defects or elemental doping. Although defects play a major role in modifying materials properties, the fact that we call them "defects" might have a negative impact. There has been a long debate on whether structurally perfect materials are equally relevant for modifying the properties and for applications. In this focus article, we clarify that although extra large amounts of defects could be detrimental to the materials properties, well-designed defects might lead to unprecedented properties and interesting applications that pristine materials do not have. Given the relatively short history of research on doped 2D layered materials, our objective is to answer and clarify the following fundamental questions: why does nanomaterial doping offer improved physico-chemical properties? What new applications arise from doping? And what are the current challenges along this line?